Inositol pyrophosphates and their unique metabolic complexity: analysis by gel electrophoresis. - Oriana Losito; Zsolt Szijgyarto; Adam Cain Resnick; Adolfo Saiardi (PLoS ONE)
Background Inositol pyrophosphates are a recently characterized cell signalling molecules responsible for the pyrophosphorylation of protein substrates. Though likely involved in a wide range of cellular functions, the study of inositol pyrophosphates has suffered from a lack of readily available methods for their analysis. Principal finding We describe a novel, sensitive and rapid polyacrylamide gel electrophoresis (PAGE)-based method for the analysis of inositol pyrophosphates. Using 4',6-diamidino-2-phenylindole (DAPI) and Toluidine Blue we demonstrate the unequivocal detection of various inositol pyrophosphate species. Conclusion The use of the PAGE-based method reveals the likely underestimation of inositol pyrophosphates and their signalling contribution in cells when measured via traditional HPLC-based techniques. PAGE-based analyses also reveals the existence of a number of additional, previously uncharacterised pyrophosphorylated inositol reaction products, defining a more complex metabolism associated with the catalytically flexible kinase class responsible for the production of these highly energetic cell signalling molecules.